A PERCEPÇÃO DOS PROFISSIONAIS DO CENTRO DE ATENÇÃO PSICOSSOCIAL ÁLCOOL E DROGAS DO MUNICÍPIO DE ANÁPOLIS SOBRE A ASSISTÊNCIA PRESTADA AO DEPENDENTE QUÍMICO - Rennan Ferreira M. e Naves; Larissa D. V. C. P. Araújo; José Dias de Araújo Neto; Edsaura Maria Pereira (Revista Educação em Saúde, 2015)
Objective: To analyze the assistance for drug users in the Centers for Psychosocial Care drug and alcoholics, to identify the professionals perception of the physical structure and assistance to users in the Centers for Psychosocial Care drug and alcoholics and to analyze the performance profile of professional the Centers for Psychosocial Care drug and alcoholics. Methods: This is a field study, prospective, transverse, exploratory, descriptive qualitative approach. The population and sample were professionals from Centers for Psychosocial Care drug and alcoholics Anápolis. The interviews were analyzed from pre categories of analysis. It was observed that professionals are mostly women with a mean age of 32 years. Results: In the majority of respondent’s view, the Centers for Psychosocial Care drug and alcoholics has an ideal structure and favorable environment for assistance to the patients, however, they pointed out some problems and difficulties in attendance, among them: deficiency of government support for the training and qualification of the professionals, low compliance of patients to the treatment, little information of the general population about the existence of Centers for Psychosocial Care drug and alcoholics in the city of Anápolis , absence of other professional specialties, low knowledge of the professionals about the model for the Centers for Psychosocial Care drug and alcoholics. Conclusion: This research can contribute to the municipality, improving the structure of Centers for Psychosocial Care drug and alcoholics as an important substitute for the conformation of network mental health component of Anápolis.